1997
DOI: 10.1002/(sici)1097-0231(199711)11:17<1926::aid-rcm97>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of corticosteroids in urine by combined solid phase microextraction/liquid chromatography/mass spectrometry

Abstract: Solid-phase microextraction combined with fast short-column liquid chromatography/mass spectrometry (SPME/LC/MS) was used for isolating and analysing 11 corticosteroids and 2 steroid conjugates from urine samples. Several SPME parameters such as polarity of fibres, extraction time and effect of ionic strength, were investigated, and their impact on the SPME/LC/MS technique was studied. To demonstrate the potential of the SPME/LC/MS method, its application to the determination of steroids in human urine was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 20 publications
4
53
1
1
Order By: Relevance
“…Previous data using diagnostic substrates have shown that P450 activities in rat, dog, monkey, and human hepatocyte suspensions are not significantly decreased by cryopreservation [6]. 10 and FMO3 at 0.2 mg of protein/ml. Protein concentration in recombinant human P450 incubations was normalized (0.25 mg/ml) using insect control protein, without esterase and P450 activity.…”
Section: Introductionmentioning
confidence: 81%
“…Previous data using diagnostic substrates have shown that P450 activities in rat, dog, monkey, and human hepatocyte suspensions are not significantly decreased by cryopreservation [6]. 10 and FMO3 at 0.2 mg of protein/ml. Protein concentration in recombinant human P450 incubations was normalized (0.25 mg/ml) using insect control protein, without esterase and P450 activity.…”
Section: Introductionmentioning
confidence: 81%
“…Steroids have been commonly analyzed using liquidliquid extraction and either ECNCI-LC/MS/MS or APCI-LC/MS/MS modes (Griffiths et al, 1999;Kim et al, 2000;Kobayashi et al, 1993;Fredline et al, 1997;Vallee et al, 2000). Influence of eluent composition on ionization efficiency has been extensively studied (Volmer and Hui, 1997).…”
Section: Analysis Of Neurosteroidsmentioning
confidence: 99%
“…Adduct ions of acetic or formic acid with analyte present in the negative ion mass spectra have been reported before [8,9]. Although the DE have been calculated for positive charged adduct ions [6], it can be argued that the abundance of acetate adduct ions, -is also related to the dissociation bond energy, and thus the proton affinity, of the bonded molecules [10].…”
Section: Resultsmentioning
confidence: 93%
“…1 for a general structure and the numbering of the C atoms) in the negative ion mode. Abundant adduct ions for these type of molecules have been reported both with the thermospray [7] as with the HN [8,9] interface. These types of compounds are chosen because the MSMS data are considered hard to interpret [15].…”
mentioning
confidence: 99%